The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.14260/jemds/2015/1701
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Alter Ation of Serum Lipid Profile in Gestational Proteinuric Hypertension

Abstract: BACKGROUND: Changes in lipid metabolism occurs in normal pregnancy during third trimester. This dyslipidemia indicative of insulin resistance is accentuated with Pre-eclampsia and Eclampsia. It contributes to both the pathogenesis of pre-eclampsia and to the risk of later-life cardiovascular disease in these patients. I have attempted to study the alterations in lipid profile in normal pregnancy, pre-eclampsia and eclampsia. MATERIALS AND METHODS: This study was conducted in Govt. Medical College for a period … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…A more recent study has compared pregnant and non-pregnant women, both of normal weight, and noted a significantly higher result for means of TG, TC, VLDL, LDLc in normal-weight pregnant women and concomitant reduction in HDLc. 14 Other studies have identified a gradual increase in lipid patterns of TG, CT, VLDL and HDLc, after the 12 th week of pregnancy, especially in the second and third trimesters, in response to estrogen stimulation and resistance to insulin and pointed to the increased TG during gestation, which suggests a correlation with the risk of pre-eclampsia and preterm birth. 15,16 It can be deduced that, for pregnant women of adequate weight, the increase or decrease in HDLc parameters will diverge in some scientific studies.…”
Section: Relation Between Physiological Disorders and Lipid Metabolismmentioning
confidence: 94%
See 1 more Smart Citation
“…A more recent study has compared pregnant and non-pregnant women, both of normal weight, and noted a significantly higher result for means of TG, TC, VLDL, LDLc in normal-weight pregnant women and concomitant reduction in HDLc. 14 Other studies have identified a gradual increase in lipid patterns of TG, CT, VLDL and HDLc, after the 12 th week of pregnancy, especially in the second and third trimesters, in response to estrogen stimulation and resistance to insulin and pointed to the increased TG during gestation, which suggests a correlation with the risk of pre-eclampsia and preterm birth. 15,16 It can be deduced that, for pregnant women of adequate weight, the increase or decrease in HDLc parameters will diverge in some scientific studies.…”
Section: Relation Between Physiological Disorders and Lipid Metabolismmentioning
confidence: 94%
“…7,26 Studies with animals may also aid scientific progress on the alterations caused by obesity. 13,14 Mertens et al 27 studied obese insulin-resistant animals with severe dyslipidemia and found a deficiency of leptin and LDL receptors in the metabolism of the animal and an increase in oxidative stress.…”
Section: Systematic Review 2010mentioning
confidence: 99%